New-Structuralist Exchange-Rate Policy and the Pattern of Specialization in Latin American Countries - Dvoskin, Ariel (2018)
The present article critically examines the transmission channels between the real ex-change rate and output growth adduced by the so-called New-Structuralist doctrine. It is shown that the assumptions under which the mechanisms work are highly restrictive, and hence, are generally inadequate to explore the problem of economic development in Latin American peripheral countries. In view of this, the potential risks associated with a policy of devaluation are warned.